1998
DOI: 10.1177/088391159801300403
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Drugs and Polymeric Drugs X: Slow Release of 5-Fluorouracil from Biodegradable Poly(γ-Glutamic Acid) and its Benzyl Ester Matrices

Abstract: We prepared poly(γ-glutamic acid)(γ-PGA) benzyl ester(γ-PBG) by the esterification of γ-PGA and benzyl bromide and evaluated the degradation behavior and its usefulness as a drug delivery system (DDS) matrix using 5-fluorouracil (5-FU) as a model drug. γ-PBG degraded in an acidic solution gradually for up to 130 days, and degraded very slowly in a phosphate buffer solution (pH 7.4). After 150 days, the weight loss of the γ-PBG film was only 10% in a phosphate buffer solution. A slow release of 5-FU from γ-PBG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…c-PGA can undergo alkaline hydrolysis by sodium hydroxide to afford c-PGA fragments with controlled molecular weights 23) . c-PGA may be applicable to polymer drugs 24) , because its benzyl ester matrices slowly release 4-fluorouracil. c-PGA powder can initiate the cationic polymerization of N-vinylcarbazol and N-vinylpyrrolidone 25) .…”
Section: Synthesis and Properties Of Polymers Consisting Of Amino Acimentioning
confidence: 99%
“…c-PGA can undergo alkaline hydrolysis by sodium hydroxide to afford c-PGA fragments with controlled molecular weights 23) . c-PGA may be applicable to polymer drugs 24) , because its benzyl ester matrices slowly release 4-fluorouracil. c-PGA powder can initiate the cationic polymerization of N-vinylcarbazol and N-vinylpyrrolidone 25) .…”
Section: Synthesis and Properties Of Polymers Consisting Of Amino Acimentioning
confidence: 99%
“…Employing B. subtilis strain F-02-1, PGA is at present biotechnologically produced by the Japanese company Meiji Seika Kaisha Ltd. Great efforts have been made to synthesize derivatives of PGA chemically. Chemical esterifications with methyl, ethyl and benzyl groups at the α-carboxylic groups resulted in derivatives of PGA with increased solubility and processible enough to prepare films (Kubota et al 1993b;Borbély et al 1994;Kishida et al 1998;Muñoz-Guerra et al 1998). By the use of crosslinking reagents [e.g.…”
Section: Commercial Significancementioning
confidence: 99%
“…H. Kubota et al [18] and S. Guerra et al [19][20][21] reported that the esterification of the carboxyl groups of g-PGA improved its solubility in organic solvents and its thermal stability. We previously reported that the g-PGA benzyl ester shows a potential for use as a DDS, [22] and that sulfonated g-PGA shows anti-thrombogenic behavior similar to heparin. [23][24][25] Furthermore, we reported an effective method for producing bionanoparticles derived from phenylalanine ethyl ester pendanted g-PGA.…”
Section: Introductionmentioning
confidence: 99%